Infrarot- und Raman-Spektren einiger Dihalogenphosphate von Zinn, Titan und Zirkon - Johann Weidlein; Kurt Dehnicke (CHIMIA)
The IR- and (in part) the Raman spectra of the dichlorophosphates [Cl3M(POCl3)O2PCl2]2 (M = Sn, Ti, Zr) and of [Br3Ti(POBr3)O2PBr2]2 are assigned according to the structures of bridged eight-membered rings.